End-of-life analysis of biodegradable plastics for industrial design purposes - Selim I., Kandikjan T., Lazarevska A. M. (My University, 2018)
Today, academic community and manufacturers are making efforts to develop plastics that have short time span in order to accommodate environmental, social and economic implications. Eventually, biodegradable plastics are gaining attention among designers and companies as materials that can imitate the benefits of petrol based plastics having the capability of degradation. The selection of these materials has influence on the production facilities, consumer use and disposal methods. These requirements are challenging, but in parallel they provide opportunities for designers in the product development process as they influence the production facilities, consumer use and disposal methods. The designers should be able to solve the problem by designing products that fulfill both the needs of biodegradability and user acceptance. In order to adopt the biodegradability requirements in the design process, the implication on the different phases of the product life cycle have to be reviewed. Unfortunately, since these materials are remarkably new in the industry, there is a lack of information for these environmental friendly materials in the literature review. Thus, in the scope of this research, based on currently available sources an adapted industrial design scheme is developed to demonstrate the end-of-life cycle analysis of biodegradable plastics.
oral presentation
Keywords: end-of-life analysis, biodegradable plastics, industrial design, user acceptance